Ungkapan Idiom Pada Novel "The Adventures Of Sherlock Holmes" Oleh Sir Arthur Conan Doyle - Ria Yuliasari; Rika Virtianti (BULLET : Jurnal Multidisiplin Ilmu, 2022)
Every language has literal and figurative meanings. Literal meaning is the direct reference of words or sentences to objects, while figurative meaning is used for giving an imaginative description or a special effect, just like idioms. This research aims at analyzing idiom expressions found in the story of The Red-headed League in The Adventures of Sherlock Holmes novel by Sir Arthur Conan Doyle and in which categories the idiom expressions belong to. The method used in this research is descriptive qualitative to analyze the idiom expressions and to categorize idiom expressions found in the novel. The analysis of idiom expressions is carried out using theory of O’Dell and McCarthy (2010:22), while the categorization of the idiom expression is carried out using theory of Loreto (1987:86) and Makkai (1972:117). From the analysis, twenty six idiom expressions are found in the story. Nineteen of them are categorized using theory of Loreto, while the other seven idiom expressions are categorized using theory of Makkai. Keywords: idiom expression, novel.